Evaluasi Kebijakan Pelayanan Publik Berbasis Hak Asasi Manusia di Kantor Imigrasi Kelas I TPI Padang - Aldaty, Lingga Septin; Putera, Roni Ekha; Aromatica, Desna (Syntax Corporation, 2025)
Policy evaluation is part of the policy cycle that plays an important role in assessing the success or failure of a policy. One form of public policy is the Regulation of the Minister of Law and Human Rights Number 25 of 2023 concerning Human Rights-Based Public Services. This study aims to evaluate the implementation of the P2HAM policy at the Class I Immigration Office of TPI Padang. This study uses a qualitative approach method with a descriptive research design. Data collection was carried out by interview, observation and documentation techniques. Data analysis was carried out using four indicators in the evaluation theory by Althaus, Bridgman and Davis, namely input, process, output, and outcome. The results of the research show that the implementation of the P2HAM Policy at the Class I Immigration Office of TPI Padang has been carried out well, but there are still some records as policy recommendations. In the Input indicator, the human resources of the P2HAM operator team have been fulfilled in terms of quality and quantity, but priority service officers are still not yet. There is no special budget for P2HAM and there are still facilities and infrastructure that are not in accordance with P2HAM rules. In the process indicators, the Class I Immigration Office of TPI Padang has implemented P2HAM in accordance with the stages in the applicable regulations. In the output indicators, the P2HAM criteria in Kanim Padang have been met and received awards and P2HAM goals have been achieved. In the outcome indicator, the implementation of the P2HAM policy at the TPI Padang Class I Immigration Office has an impact on changes in the service system, improving human resource competence, improving accessibility and infrastructure facilities and improving the quality of services to the public in a better direction and in accordance with human rights principles.